Análisis de la prominencia malar en tejidos blandos y su correlación con tejidos duros en adultos jóvenes - Lina Maria Moreno-Uribe; Julian David Vasquez-Yasser; Nelson Cortes-Castaño (Universidad de Antioquia, 1995)
The malar bones have been traditionally evaluated in a clinical way, which is very subjective since several studies have not found any direct relation between the malar prominence in hard and soft tissues, especially having the later a variable with. The purpose of this study is to establish the radiographic values for the malar soft tissue prominence in young Colombian adults. Two linear measurements (Mp FIB and Pr - O - Mp in mm) and two angular measurements (S - N - Pm, Mp - N - Sn) were taken in soft tissues. Two angular measurements (S - N - A and S - N - O) and one linear mesautement (O-N-A) were taken for hard tissues using cephalograms of 106 well balanced students of the University of Antioquia. The correlation among soft and hard tissues show that the soft tissues of the malar bones and Subnasal point folloe a pattern similar to their subjacent bony structures. A complete independence was found between the malar complex and the dentoalveolar process both in hard (Point A) and soft tissues (Subnasal). This type of evaluation should be used in patients who need maxillary surgery (Lefort) to establish the height of the incision according to the degree of hipoplasia presented.